Preventivna diplomacija Slovenije pri reševanju vprašanja samostojnosti in neodvisnosti Kosova (2007-2010) - Zupančič, Rok (Teorija in praksa, 2011)
The article analyses the preventive diplomacy of Slovenia applied during the period Kosovo was preparing to declare its independence, as well as in the months that followed. In the first half of 2008, when the question of independence was the most pressing and when independence was finally declared, Slovenia was performing one of the most demanding foreign policy tasks in its history - presiding over the EU Council. The methodology is based on two methods: first, on an analysis of press releases of the Ministry of Foreign Affairs of Slovenia; and second, on an analysis of semi-structured interviews with high-ranking Slovenian diplomats who were actively engaged in preventive diplomacy in the case of Kosovo. The analysis shows that Slovenia exercised a continuous "policy of balancing" between Kosovo and Serbia, in constant co-ordination with some influential EU countries, as well as with the USA and the Russian Federation. Slovenia's quite active inclusion in that process was possible because of the credibility the country enjoys in South-east Europe, as well as the quality of information about Kosovo's declaration of independence Slovenia had. However, it must be noted that Slovenia was left out of certain negotiations on Kosovo's declaration of independence despite the fact that it was presiding over the EU Council.
Keywords: Diplomacija; Diplomacy; Conflict resolution; Reševanje konfliktov; Confederation of New Trade Unions of Slovenia "Independence"; Independence; Neodvisnost; Slovenia; Slovenija; Kosovo